Experimental evaluation of the efficiency of boron in controlling the reactivity of water-cooled nuclear reactors (Research, Society and Development, 2022)
Nuclear reactors are devices in which chain fission reactions are obtained in a controlled manner. The unit that this control represents is the reactivity. By inserting or removing neutron absorber bars the neutron flux is controlled, thereby determining the power levels. Already for long-term control, chemicals with a high absorption cross section are dissolved in the cooling water of the pressurized water reactor (PWR). Boric acid is used for this purpose, due to the B-10 isotope. The purpose of this work was to presents the effectiveness of boron in controlling the reactivity of nuclear reactors cooled to light water. Samples with different concentrations of boric acid were inserted into the IPR-R1 Triga nuclear reactor core from the Development Center of Nuclear Technology (CDTN). Variations of reactivities were evaluated using the Static Reactivity Null Method. The pH and electrical conductivity measurements were performed on the solutions to characterize them. The results obtained made it possible to simulate B-10 consumption during reactor operation and its effect on reactivity with increasing boric acid concentration. The pH values had a very small increase after irradiation. However, the conductivity of the samples had minor changes. As a result of this research, a correlation between various concentrations of boric acid and reactivity of the reactor was raised.